Factors Associated with General Sexual Functioning and Sexual Satisfaction among People Living with HIV: A Systematic Review. Issue 7 (1st September 2020) - Huntingdon, Ben; Muscat, Danielle Marie; de Wit, John; Duracinsky, Martin; Juraskova, Ilona
ABSTRACT: Sexual difficulties, experienced by half of the people living with HIV (PLWH), not only affect quality of life but have been associated with lower adherence to antiretroviral medication. This systematic review synthesizes studies published since 1997 which used statistical methods to investigate factors associated with general sexual functioning or sexual satisfaction of PLWH. We searched Medline, PsycINFO, Embase, Cinahl and Scopus with terms: HIV AND sexual dysfunction AND factors. Of 5552 records, 26 studies met selection criteria. Twenty-one studies on general sexual function, and five studies on sexual satisfaction. Two researchers separately extracted data and applied standardized quality assessment criteria. (Registration: CRD42018094146.) Regarding general sexual dysfunction, older age, general physical health, depression, body image and psychological distress were the most relevant factors. There was inconsistent evidence for: CD4, viral load, HIV symptom severity, HIV disease progression and time since diagnosis. From limited available evidence on sexual satisfaction, age, unemployment, and psychosocial factors were significant. Overall, anxiety and relational factors were under-researched, treatment center studies were over-represented and non-validated measurement of outcomes was common. Future research is required to build theoretical models of sexual well-being specific to PLWH to guide effective research and intervention to promote sexual quality of life of PLWH.